Natural history of the parasite Waddycephalus in the Townsville region of north-east Australia - Halvard Aas Midtun; Megan Higgie; Conrad Hoskin (Parasitology, 2023)
Waddycephalus is an understudied genus of pentastomids native to Australia and south-east Asia. The genus was recognized in 1922 but there has been little research on these pentastomid tongue worms over the last century. A few observations suggest a complex life cycle through 3 trophic levels. We aimed to add knowledge to the Waddycephalus life cycle in woodland habitats in the Townsville region of north-east Australia. We used camera trapping to identify the most likely first-intermediate hosts (coprophagous insects), we conducted gecko surveys to identify multiple new gecko intermediate host species and we dissected road-killed snakes to identify additional definitive hosts. Our study paves the way for further research into the intriguing life cycle of Waddycephalus, investigation of spatial variation in prevalence and impacts of the parasite on host species.